A prospective study of P-POSSUM score in predicting morbidity and mortality in patients undergoing gastrointestinal surgeries - Vatnala, Vishwaja; Gatla, Naga Samrat; Hota, Prasan Kumar; B., Ramaswami; P., Venkat Lalu; V., Pradeep (International Surgery Journal, 2026)
Background: The comparison of morbidity and mortality rates is an essential component of the surgical audit using severity scores, which helps in risk prediction, identification of patients with unexpected outcomes, and improving clinical decisions. The objective was to determine the accuracy of the Portsmouth-physiological and operative severity score for the enumeration of mortality and morbidity (P-POSSUM score) in predicting the anticipated morbidity and mortality rate and to compare it with the actual morbidity and mortality rate in patients undergoing gastrointestinal surgeries in the Indian population. Methods: This study was conducted over 02 years at Mamata General Hospital. It included 80 patients who were clinically suspected cases of gastrointestinal diseases and underwent both elective and emergency gastrointestinal surgeries. Diagnosis was based on history, thorough physical examination and routine investigations. Operative parameters like operative severity, number of procedures, blood loss, peritoneal soiling, presence of malignancy, and mode of surgery were recorded for each patient as per a predetermined proforma. Patients were followed-up for a period of 30 days post-surgery. Results: The commonest age group of the study population was less than 60 years (45%) followed by 61 to 70 years (43.8%). The male-to-female ratio was 1.6:1. The majority of the cases were of gastrointestinal perforation (22.4%) and cholelithiasis (22.4%). Surgical site infections (SSIs) were the most commonly encountered postoperative complications (55.6%). Only 05 cases of mortality were encountered. Among physiological severity parameters, systolic blood pressure, pulse rate, haemoglobin level, total leucocyte count, serum urea, and serum sodium were significantly associated with morbidity and mortality. Among operative severity parameters, blood loss, peritoneal soiling and mode of surgery were significantly associated with morbidity and mortality. Conclusions: The P-POSSUM scoring system is a useful tool for surgical risk stratification and helps in predicting morbidity and mortality in patients undergoing gastrointestinal surgeries.